Pseudovascular Revelation of Seropositive Neuromyelitis Optica Spectrum Disorder: A Case Report - Haddouali, Kamal; Sguiar Lhamdani, Nour El Houda; Bellakhdar, S.; El Otmani, Hicham; El Moutawakil, Bouchra; Rafai, Mohammed Abdoh (International Journal of Innovative Research in Medical Science, 2024)
Symptom onset in Neuromyelitis Optica spectrum disorder (NMOSD) is often acute, while sudden onset is rare and suggests vascular causes. We report the case of a 63-year-old woman who had two sudden attacks, blindness in the left eye and weakness of the lower limbs. The presence of a diencephalic hypersignal around the third ventricle and a bright spotty lesion on the MRI had evoked the NMOSD diagnosis which was confirmed by positive anti-aquaporin 4 antibodies in the serum. The patient was treated with cyclophosphamide with no relapses after 6 months of treatment. Few case reports have been published on this subject, testifying to the rarity of this "pseudo-vascular" mode of revelation of NMOSD, which may be a source of diagnostic error or delay.